2020
DOI: 10.1016/j.archger.2020.104204
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and prognostic factors of COVID-19 infection in an elderly hospitalized population

Abstract: Highlights Older patients with COVID infection have a similar clinical course than younger subjects. Males have a greater COVID mortality than females. Worsening dyspnea and decline renal function during admission associate with death. Treatment with RAAS inhibitors associates with a greater survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 18 publications
10
47
1
1
Order By: Relevance
“…In this study, we assessed the clinical characteristics at the admission of patients with more severe infections admitted to our hospital in the first wave of the COVID-19 pandemic. The overall proportion of deaths was 32%, much higher than that observed in China [ 4 , 5 ], similar to that reported in other areas of Spain [ 6 , 7 , 8 ] and neighboring European countries [ 9 , 10 ], and lower than that reported in United States [ 11 ], for the same age ranges. The threshold of severity required for hospitalization could explain some of these differences, as too could the incomplete follow up of patients assessed in some studies.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we assessed the clinical characteristics at the admission of patients with more severe infections admitted to our hospital in the first wave of the COVID-19 pandemic. The overall proportion of deaths was 32%, much higher than that observed in China [ 4 , 5 ], similar to that reported in other areas of Spain [ 6 , 7 , 8 ] and neighboring European countries [ 9 , 10 ], and lower than that reported in United States [ 11 ], for the same age ranges. The threshold of severity required for hospitalization could explain some of these differences, as too could the incomplete follow up of patients assessed in some studies.…”
Section: Discussionsupporting
confidence: 75%
“…We highlight the high proportion of institutionalized patients in our sample (61%), re ecting a population with greater clinical fragility and therefore with less ability to respond to an organic stressor. Thus, the series reported by Gutiérrez-Rodríguez et al (11) had a mortality (41%) and a proportion of institutionalized patients (70%) more similar to those of our sample than those reported by Mostaza et al (mortality 35% and proportion of institutionalized 23%) (20). In neighbouring countries, Zerah et al (France) (29) reported a lower lethality (31%) in a cohort of 821 hospitalized patients aged 70 or older, although with a proportion of institutionalized patients much lower than our sample (29%).…”
Section: In-hospital Mortalitysupporting
confidence: 85%
“…Previous treatments have not been evaluated as prognostic factors in the before mentioned trials(9-11) so we cannot compare our results with them. In a younger cohort, Mostaza et al (20), in people older than 75 years, did nd a better prognosis in patients who previously took reninangiotensin-aldosterone system antagonists. Regarding previous chronic diseases, our results are similar to the study by Ramos-Rincon et al (9); however, Covino et al (10) reported severe dementia as an independent risk factor for death, although age, since it was not apparently included in their multivariate analysis, cannot be rule out as a confounding factor.…”
Section: Predictors Of Severe Disease and Mortalitymentioning
confidence: 91%
“…Prognostication of COVID-19 mortality is currently being heavily investigated such that patient risk and outcomes may be further stratified. Some prognostic factors associated with mortality in patients infected with SARS-CoV-2 include elevated CRP, LDH, and aminotransferases, acute onset of symptoms, fever and dyspnea, tachypnea, low oxygen saturation on admission, and lower platelet count [29 , 30] . Although these data were published several months following the death of our patient, it appears that our patient had several significant prognostic factors associated with increased mortality, such as elevated CRP, LDH, tachypnea, cerebrovascular disease, low oxygen saturation on admission, and acutely progressive disease.…”
Section: Discussionmentioning
confidence: 99%